2018
DOI: 10.1177/0961203318768888
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous pulses of methylprednisolone to treat flares of immune-mediated diseases: how much, how long?

Abstract: Introduction Glucocorticoids are widely used in the treatment of immune-mediated diseases. Despite their widespread use, details on dosing, effectiveness and adverse effects are yet to be determined. Objective To know the current use of methylprednisolone (MTP) in the management of immune-mediated conditions, evaluating the relationship among doses, therapeutic response and adverse effects. Methodology A multicenter retrospective cohort study was designed, including patients who received intravenous pulses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
9
0
3
Order By: Relevance
“…evaluating 55 lupus patients found that patients receiving high-dose pulses (1 g/day for 3 days) had more frequent infections than those with lower doses (≤1500 mg for the three consecutive days). 42 Similar results were found in a recent study from Uruguay, showing lower rates of infections among patients treated with pulses of 500 mg or less each compared with 1000 mg. 43 In the RELES study, methyl-prednisolone pulses did not show an independent effect on the risk of infection; 36 however, they did in the GLADEL cohort. 37 As half the patients treated with pulses in the RELES cohort received less than 1000 mg/day for 3 days, 36 it is possible that the use of different doses of methyl-prednisolone explain the discrepancy.…”
Section: Clinical Effects Of Glucocorticoids In Slementioning
confidence: 91%
“…evaluating 55 lupus patients found that patients receiving high-dose pulses (1 g/day for 3 days) had more frequent infections than those with lower doses (≤1500 mg for the three consecutive days). 42 Similar results were found in a recent study from Uruguay, showing lower rates of infections among patients treated with pulses of 500 mg or less each compared with 1000 mg. 43 In the RELES study, methyl-prednisolone pulses did not show an independent effect on the risk of infection; 36 however, they did in the GLADEL cohort. 37 As half the patients treated with pulses in the RELES cohort received less than 1000 mg/day for 3 days, 36 it is possible that the use of different doses of methyl-prednisolone explain the discrepancy.…”
Section: Clinical Effects Of Glucocorticoids In Slementioning
confidence: 91%
“…Methylprednisolon ist ein Standardmedikament zur Induktionstherapie diverser Autoimmunerkrankungen. Insbesondere der schnelle Wirkungseintritt begünstigt das Erreichen einer zügigen Remissionsinduktion [9]. Cyclophosphamid (CYC) ist bei eosinophiler Granulomatose mit Polyangiitis (EGPA) mit schwerer Organbeteiligung die Therapie der Wahl [10].…”
Section: Diskussionunclassified
“…The “classical” standard 1 mg/kg/day prednisone dose is not supported by either basic pharmacology or clinical evidence ( Figure 1 ) [ 19 , 20 ]. It is unlikely that anti-inflammatory effects increase significantly after prednisone doses have reached 30–40 mg/day, since such doses already result in a saturation of almost 100% of the genomic pathway [ 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The “classical” standard 1 mg/kg/day prednisone dose is not supported by either basic pharmacology or clinical evidence ( Figure 1 ) [ 19 , 20 ]. It is unlikely that anti-inflammatory effects increase significantly after prednisone doses have reached 30–40 mg/day, since such doses already result in a saturation of almost 100% of the genomic pathway [ 12 , 19 ]. Recent data suggest that higher initial doses of prednisone are associated with higher cumulative doses [ 21 ] with the well proven result of increasing damage accrual [ 1 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation